Curettage and bone grafting combined with electrocautery and drill, supplemented with plate fixation for the treatment of pediatric humeral aneurysmal bone cysts: a retrospective study - Liang, Mengxue; Shi, Jia; Ni, Xuewen; Zhang, Li; He, Zuojia; Chen, Jiaqi; Huang, Hua; Pu, Feifei (Frontiers in Pediatrics, 2025)
BackgroundAneurysmal bone cysts (ABCs) are benign, locally aggressive bone lesions that predominantly affect children and adolescents. The humerus is a common site, and treatment aims to eradicate the lesion while preserving growth potential and function. This study aimed to evaluate the clinical efficacy of curettage and bone grafting combined with electrocautery and burr drilling, supplemented with plate fixation, for treating pediatric humeral ABC.MethodsA retrospective analysis was conducted on 23 pediatric patients diagnosed with humeral ABC who underwent this surgical procedure. Inclusion criteria were age ≤18 years, a confirmed diagnosis via imaging and histopathology, and the absence of epiphyseal or joint surface involvement. The surgical techniques involved thorough curettage, electrocautery, burr drilling, bone grafting, and plate fixation. Postoperative follow-up included pain assessment using the Visual Analog Scale (VAS), functional evaluation using the Constant-Murley score, and radiographic imaging to assess bone healing and recurrence.ResultsThe average patient age was 8.6 years, and the mean follow-up period was 35.8 months. Postoperative pain scores (VAS) significantly decreased from a preoperative average of 5.6–1.1 at 1-year post-surgery (P < 0.05). Functional recovery, measured by the Constant-Murley score, improved from a preoperative average of 42–87 at 1-year post-surgery (P < 0.05). Radiographic evaluation confirmed complete lesion clearance and bone fusion in all patients, with no recurrence observed during the follow-up period. The overall complication rate was 17.39%, including one case of infection, two cases of wound dehiscence, and one case of transient radial nerve palsy, all of which were resolved with appropriate treatment.ConclusionThe combination of curettage, bone grafting, electrocautery, burr drilling, and plate fixation is a safe and effective treatment for pediatric humeral ABC. This approach ensures thorough lesion removal, promotes bone healing, and minimizes recurrence, making it a viable option for clinical application.